Pengaruh Kompensasi Manajemen, Inventory Intensity Ratio, dan Profitabilitas Pada Tax Avoidance - Indriyanti, Komang Dessica; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p27, 2019)
The purpose of this study is to examine the effect of management compensation, inventory intensity ratio, and profitability on tax avoidance. This research was conducted at a manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2013-2017. The number of observations obtained was 205 observations using the nonprobability sampling method, namely purposive sampling. The data analysis technique used is multiple linear regression analysis. The results of multiple linear regression analysis show that management compensation has a negative effect on tax avoidance, profitability has a positive effect on tax avoidance, while the inventory intensity ratio does not affect tax avoidance. Keywords : Management compensation, inventory intensity ratio, profitability, tax avoidance